Oxidative stress and antioxidant indices of marine alga Porphyra vietnamensis - Pise, Navnath M.; Gaikwad, Dattatry K.; Jagtap, Tanaji G. (Acta Botanica Croatica, 2013)
Oxidative stress and antioxidant defence systems were assessed in a marine red alga Porphyra vietnamensis Tanaka et Pham-Hoang Ho, from India. Lipid peroxidation (LPX) and hydrogen peroxide (H2O2) were measured as oxidative stress markers. Antioxidant defences were measured as catalase (CAT), glutathione S-transferase (GST) and ascorbic acid (AsA), in order to understand their dissimilarity with respect to environmental conditions (pollution levels) from selective locations along the central west coast of India. Levels of LPX, H2O2, CAT and GST were significantly higher in samples collected from Dona Paula than in samples from Malvan and Kunkeshwar, while a lower concentration of AsA was found in samples from Dona Paula. Heavy metals such as Cd, Pb and Hg in higher concentrations in these areas than in other sites were also observed. Variation of oxidative stress indices in response to the accumulation of heavy metals within P. vietnamensis could be used as molecular biomarkers for the assessment and monitoring of environmental quality in ecologically sensitive marine habitats.